Stiffness regulates the proliferation and osteogenic/odontogenic differentiation of human dental pulp stem cells via the WNT signalling pathway. (17th January 2018) - Liu, Nanxin; Zhou, Mi; Zhang, Qi; Zhang, Tao; Tian, Taoran; Ma, Quanquan; Xue, Changyue; Lin, Shiyu; Cai, Xiaoxiao
Abstract: Objectives: Researches showed that stiffness of the extracellular matrix can affect the differentiation of many stem cells. Dental pulp stem cells (DPSCs) are a promising type of adult stem cell. However, we know little about whether and how the behaviour of DPSCs is influenced by stiffness. Materials and methods: We carried out a study that cultured DPSCs on tunable elasticity polydimethylsiloxane substrates to investigate the influence on morphology, proliferation, osteogenic/odontogenic differentiation and its possible mechanism. Results: Soft substrates changed the cell morphology and inhibited the proliferation of DPSCs. Expression of markers related to osteogenic/odontogenic differentiation was significantly increased as the substrate stiffness increased, including ALP (alkaline phosphatase), OCN (osteocalcin), OPN (osteopontin), RUNX‐2 (runt‐related transcription factor‐2), BMP‐2 (bone morphogenetic protein‐2), DSPP (dentin sialophosphoprotein) and DMP‐1 (dentin matrix protein‐1). Mechanical properties promote the function of DPSCs related to the Wnt signalling pathway. Conclusions: Our results showed that mechanical factors can regulate the proliferation and differentiation of DPSCs via the WNT signalling pathway. This provides theoretical basis to optimize dental or bone tissue regeneration through increasing stiffness of extracelluar matrix.